Characteristics of municipal solid waste - Agamuthu, P. (Malaysian Journal of Science, 1999)
This paper describes the general features of three Municipal Solid Waste (MSW) landfills in Malaysia, the MSW composition in these landfills and the leachate characteristics. Typical of most Asian countries (except Japan), the MSW comprised 60-90 % organic waste, mainly garbage or agro-industrial waste, with 3 to 18 % plastic waste. Detailed evaluation of the landfill leachate revealed that the concentrations of Na, K and Cl are exceptionally high and thus some form of pretreatment of the leachate before biological treatment is suggested. Urban wastes from the city of Kuala Lumpur (KL) and adjacent satellite town of Petaling Jaya (PJ) contribute higher pollution parameters in the leachate compared to the suburban landfill in Sabak Bernam (SB).